Soluble iC3b as an early marker for pancreatic adenocarcinoma is superior to CA19.9 and radiology - Märten, Angela; Büchler, Markus W.; Werft, Wiebke; Wente, Moritz N.; Kirschfink, Michael; Schmidt, Jan (Journal of immunotherapy, 2010)
Pancreatic adenocarcinoma as an aggressive tumor still lacks specific markers. Resection offers the only potential cure, and earlier diagnosis could benefit many patients. Here, we analyzed siC3b as a potential diagnostic marker. Soluble iC3b is generated in the fluid phase after binding of autoantibodies to tumor cells and subsequent inactivation of the complement cascade by interaction with complement regulatory proteins. Two hundred thirty-two plasma samples from patients with adjuvant treatment after resection, from healthy volunteers, and from vulnerable patients were collected prospectively and analyzed for siC3b. Every 3 months, the patients underwent imaging and the results from siC3b enzyme-linked immunosorbent assay were categorized according to radiologically defined recurrence within 4 months after blood withdrawal. Furthermore, the regulatory factors of the complement system were analyzed in tumor cells and in urine. The most important finding was that up to 4 months before radiologically defined recurrence, siC3b plasma level is increased with a sensitivity and specificity resulting in an area under the curve of 0.85, which could be further increased by combining it with CA19.9 (area under the curve=0.92). Complement regulatory proteins are highly expressed in pancreatic carcinoma cells and detectable in the patient's urine. In summary, screening for siC3b in patients with an increased risk for pancreatic ductal adenocarcinoma (patients with chronic pancreatitis, hereditary pancreatitis, after curative resection, and patients with a variety of familial cancer syndromes) allows for early detection with high sensitivity, as siC3b plasma levels are increased up to 4 months before radiologic evidence. Sensitivity could be further increased by combining this approach with CA19.9.